Role of maternal and neonatal plasma vitamin D levels on development of neonatal sepsis in term infants - Charoo, Bashir Ahmad; Ganaie, Aijaz Hamid; Lone, Parvez Ahmed (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal sepsis is characterized by signs and symptoms of infection with or without accompanying bacteremia in the first month of life and is an important cause of morbidity and mortality. There is overwhelming experimental evidence that vitamin D has an important role in the regulation of both the innate and acquired immune systems. Therefore, low vitamin D status is expected to be one of the risk factors for neonatal sepsis. Methods: Between September 2016 and July 2018 term infants with clinical and laboratory findings of Neonatal Sepsis who were>37weeks of gestational age and were admitted to Neonatal Intensive Care Unit of Sheri-Kashmir Institute of Medical Sciences Soura, Srinagar and healthy infants (controls) who presented to our out-patient clinic for routine evaluation with no signs of clinical and laboratory infection were taken up for study. Blood for neonatal and maternal vitamin D levels was obtained from all infants and their mothers at the postpartum period at the time of hospital admission. Results: A total of 92 mother-neonatal pairs (46 cases and 46 controls) were enrolled in the study. In the study group the mean neonatal vitamin D level was 12.90 ng/ml and the mean maternal vitamin D level was 22.90 ng/ml. In the control group the mean neonatal vitamin D level was 25.99 ng/ml and the mean maternal vitamin D level was 37 ng/ml. Mean maternal and neonatal vitamin D levels were significantly lower in the study group than in the control group. Conclusions: There was a highly significant correlation between neonatal and maternal vitamin D levels in both study and control groups in our study. Thus, it was concluded that babies born to mothers with inadequate vitamin D levels have inadequate vitamin D levels.